2020
DOI: 10.1021/acs.chemmater.0c00648
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reactivity under Confinement Enabled by Molecularly Pillared 2D and Layered Materials

Abstract: This perspective presents an overview of how confinement can be used to tune electrochemical reactivity and the concept of using molecularly pillared 2D and layered materials to experimentally study this phenomenon. Many theoretical and computational studies have shown that the confinement of liquid-phase reactants to nano-or subnanometer spaces influences their electrochemical reactivity. While confinement is ubiquitous in various high surface area materials used as electrodes, experimental studies of this ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 99 publications
1
33
0
Order By: Relevance
“…(III) Insertion of guest molecules to open the interlayer space for electrolytes also serves as an important strategy to make more MXene nanosheet surfaces electrochemically accessible (Figure c), and these types of interlayer space engineering are referred to as pillaring methods. , The approaches used to introduce intercalants into MXene gallery comprise spontaneous/electrochemical intercalation and chemical transformation, and in MXene-based electrodes, the pillaring reagents include metal cations (Sn 2+ , Sn 4+ , Co 2+ , Na + , etc . ), ,, positively charged molecules or polymers (quaternary ammonium salts, ionic liquids, etc .…”
Section: Intercalation Chemistry In the Applications Of Mxenesmentioning
confidence: 99%
“…(III) Insertion of guest molecules to open the interlayer space for electrolytes also serves as an important strategy to make more MXene nanosheet surfaces electrochemically accessible (Figure c), and these types of interlayer space engineering are referred to as pillaring methods. , The approaches used to introduce intercalants into MXene gallery comprise spontaneous/electrochemical intercalation and chemical transformation, and in MXene-based electrodes, the pillaring reagents include metal cations (Sn 2+ , Sn 4+ , Co 2+ , Na + , etc . ), ,, positively charged molecules or polymers (quaternary ammonium salts, ionic liquids, etc .…”
Section: Intercalation Chemistry In the Applications Of Mxenesmentioning
confidence: 99%
“…Finally, tuning the interlayer of layered materials by restacking of 2D materials with interlayer pillars provides an opportunity to modulate the confinement environment in terms of its geometry and size. [ 203 ] Owing to the synergistic electronic effect and surface configuration between the intercalated ions and the layers, it is expected to induce high surface area and more active site to yield high electrochemical activity. For example, systematic experimental research indicated that Ni 2+ intercalated in birnessite MnO 2 could exhibit OER performance superior to that of pristine birnessite.…”
Section: Summaries and Outlookmentioning
confidence: 99%
“…31 The findings give valuable guidance for the design of high-power intercalation hosts, such as interlayer-functionalized materials with increased interlayer spacing. 32,33 Based on these observations, a clear link between the electrochemical intercalation kinetics and the electrochemically induced deformation behavior can be made. The kinetics of the lithiation reaction are diffusion-limited when the host material expands/contracts, i.e., undergoes deformation, and they become more and more non-diffusion-limited (pseudocapacitive) when the interlayer is expanded and no more volumetric changes occur in the host material lattice.…”
mentioning
confidence: 99%